If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(m + 2) = 40 Reorder the terms: 4(2 + m) = 40 (2 * 4 + m * 4) = 40 (8 + 4m) = 40 Solving 8 + 4m = 40 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 4m = 40 + -8 Combine like terms: 8 + -8 = 0 0 + 4m = 40 + -8 4m = 40 + -8 Combine like terms: 40 + -8 = 32 4m = 32 Divide each side by '4'. m = 8 Simplifying m = 8
| 3x^3+25x^2+8x=0 | | g/2+3=15 | | 3a+12=38 | | 0.50X+0.45(40)=0.25(150) | | 3x+4=2x-24 | | 2x(x-5)=3 | | 3t-24=57 | | 8x+9=-143 | | 3v+17=35 | | 4v+14=32 | | 12+4x-8=48 | | ad= | | y=x^3-27x+4 | | 6(4-8a)+7=-17 | | -3x^2+8x-2=0 | | (7)(4+2x)=56 | | 64m^8-49n^6=0 | | -(9x-8)= | | -6x-5x=-11 | | -8=3x+4 | | 12x+6y=60 | | -15x^3+40x^2+35x=0 | | -35=n-17 | | -6=3(3+k) | | 6-(-10)= | | 5-4x-5=-8 | | -77=8x+3 | | -126=-18r | | -11=x-6 | | w^2-6w-8=0 | | 7a+8=57 | | 4(3-x)-8=5-(3x-2) |